Unlawful Act of Taking Control of Land Belonging to Another Person Without Proof of Ownership (Study of Decision Number 96/Pdt.G/2024/PN Gto) - Igirisa, Marshanda (Ilmu Hukum Prima (IHP), 2025)
Unlawful acts have been around for a long time, but it took a very long time for the formulation of illegal acts to apply generally. In Indonesia, PMH has been regulated in 1365 of the Civil Code. Many unlawful acts lawsuits have been submitted to the Court, one of which is a case of illegal acts with the object of a land dispute. Land is an asset or property with a high selling value occasionally. One of the PMH cases with the object of a land dispute is Decision Number 96 / Pdt.G / 2024 / PN Gto. In this case, we look at the position of the case and the legal decision handed down by the panel of judges at the first instance court. This study uses normative legal research with data collection techniques using literature studies. The results obtained are the recognition of land made by the defendants because the defendants believe that the land is the legacy of their grandfather, when in fact, the defendants' grandfather only borrowed the land; the panel of judges has also considered all elements and accepted all the plaintiffs' claims.